1983
DOI: 10.1056/nejm198311103091905
|View full text |Cite
|
Sign up to set email alerts
|

Rationing Intensive Care — Physician Responses to a Resource Shortage

Abstract: To determine how physicians ration limited critical resources, we studied the allocation of intensive-care-unit (ICU) beds during a shortage caused by a lack of nurses. As the bed capacity of the medical ICU decreased from 18 to 8, the percentage of days on which one or more beds were available decreased from 95 to 55 per cent, and monthly admissions decreased from 122 to 95. Physicians responded by restricting ICU admissions to acutely ill patients and reducing the proportion of patients admitted primarily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(91 citation statements)
references
References 10 publications
4
83
0
3
Order By: Relevance
“…Though there is a substantial literature on resource allocation and utilisation in ICUs including the assessment and predictors of outcome, [1][2][3][4][5][6][7][8][9][10][11][12] and guidelines for triage of critically ill patients and ICU admissions and discharges, 11 13 we are unaware of any research that describes actual priority setting in an ICU with particular reference to neurosurgery patients.…”
mentioning
confidence: 99%
“…Though there is a substantial literature on resource allocation and utilisation in ICUs including the assessment and predictors of outcome, [1][2][3][4][5][6][7][8][9][10][11][12] and guidelines for triage of critically ill patients and ICU admissions and discharges, 11 13 we are unaware of any research that describes actual priority setting in an ICU with particular reference to neurosurgery patients.…”
mentioning
confidence: 99%
“…Exogenous sources of variability identified thus far include variable blood volume in the QFT TB antigen tube, variable vigor of tube shaking, and processing delay (2). Endogenous immunomodulators originating from the host remain unknown.…”
Section: To the Editormentioning
confidence: 99%
“…With rising demand for critical care, intensivists' time must increasingly be divided among patients (1)(2)(3)(4)(5)(6). Recent studies suggest that increased strain at intensive care unit (ICU) admission leads to higher mortality in closed ICUs (7) and that increased strain at discharge leads to increases in ICU readmissions (8).…”
Section: The Allocation Of Intensivists' Rounding Time Under Conditiomentioning
confidence: 99%
“…A large study of the APACHE database demonstrated no association between bed availability and ICU mortality (3). However, decreased ICU bed availability has been shown to be associated with increased severity of illness in patients admitted to the ICU (4), (5), (6), suggesting that bed availability plays a role in triage decisions. Some studies have demonstrated a shorter ICU length of stay associated with limited bed availability, which may indicate increased pressure to discharge patients when beds are limited (3), (5), (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, decreased ICU bed availability has been shown to be associated with increased severity of illness in patients admitted to the ICU (4), (5), (6), suggesting that bed availability plays a role in triage decisions. Some studies have demonstrated a shorter ICU length of stay associated with limited bed availability, which may indicate increased pressure to discharge patients when beds are limited (3), (5), (6). Finally, one study of a neurological ICU demonstrated an association between increased patient flow rates and increased rates of readmission to the ICU (7).…”
Section: Introductionmentioning
confidence: 99%